PERANCANGAN SISTEM INFORMASI ARSIP MENGGUNAKAN METODE ZACHMAN FRAMEWORK (STUDI KASUS BPN CIAMIS) - Rizal Zafar Gimnastiar; Nana Yudi Permana; Maulana Siddiq (Jurnal Mahasiswa Sistem Informasi Galuh, 2026)
This research aims to design a web-based archival information system using the Zachman Framework approach. The framework is selected because it provides a comprehensive perspective in analyzing system requirements from different viewpoints, including the owner, planner, and designer perspectives. The research stages include identifying data entities, designing use case diagrams, activity diagrams, class diagrams, sequence diagrams, and developing user interface wireframes. Each stage is structured systematically to produce a system design that aligns with the organizational needs. The results show that the designed system is capable of mapping essential data requirements, such as incoming letters, outgoing letters, dispositions, and digital archives.